Reducing network congestion by separating nets of single-row networks into layers - Noraziah, Ahmad; Herawan, Tutut; Noriyani, Mohd Zin; Mustafa, Mat Deris; Zailani, Abdullah (Elsevier Ltd., 2011)
Single-row routing is a method for routing pair of nodes set in a single-row axis. The nets construct the wire without traverse each other in the printed circuit board design that has been drawn from left to right. The main purpose in single-row routing is to achieve the optimal results of minimum congestion arise from the number of horizontal tracks in the network. Optimal results for a single layer network have been achieved through a model called Enhanced Simulated Annealing Single-row Routing (ESSR). However, a single layer model suffers from non-tolerable lower bound values with high congestion depending on the network size. These results may further be improved by partitioning the network into two or more layers. In this paper, a technique for partitioning the nodes from a single-row network into several layers of planar graphs by using k-means algorithm has been proposed. The experiment result shows that the proposed technique is able to minimize the network congestions.